The type 2 diabetes ‘modern preventable pandemic’ and replicable lessons from the COVID-19 crisis - Michael E. Singer, Ph.D.; Kevin A. Dorrance, M.D.; Monica M. Oxenreiter; Karena R. Yan; Kelly L. Close (Preventive Medicine Reports, 2022)
To frame the substantial prevalence of type 2 diabetes (T2D) as a ‘Modern Preventable Pandemic’ (MPP) and present certain replicable policy lessons from the COVID-19 crisis to address it. A literature and policy review was performed to analyze data about the COVID-19 and T2D pandemics to establish their multi-factorial health, social, and economic impacts. With the global prevalence of T2D tripling in the last two decades, T2D has become an MPP largely due to modifiable human behaviors. Certain successful elements of the response to the COVID-19 pandemic provide important lessons that can be adapted for the growing T2D MPP. With proper education and access to resources, it is possible to mitigate the T2D MPP through focused government policies as illustrated by many of the lessons of the COVID-19 pandemic response. Without such government intervention, the T2D MPP will continue to grow at an unsustainable pace with enormous health, social and economic implications. Immediate action is necessary. The scale of the T2D pandemic warrants a robust response in health policy as outlined through eight coordinated efforts; the lessons of the COVID-19 crisis should be studied and applied to the T2D MPP.